Sex differences in hypertension among people living with HIV after initiation of antiretroviral therapy - Masenga, Sepiso K.; Povia, Joreen P.; Mutengo, Katongo H.; Hamooya, Benson M.; Nzala, Selestine; Heimburger, Douglas C.; Munsaka, Sody M.; Elijovich, Fernando; Patel, Kaushik P.; Kirabo, Annet (Frontiers in Cardiovascular Medicine, 2022)
Background Hypertension is common in people living with HIV (PLWH) on antiretroviral therapy (ART). In the general population and in experimental animal models, the incidence of hypertension is greater in males than in females, especially during the premenopausal period. However, it is not known whether there are sex differences in hypertension associated with HIV and ART, and the factors contributing to incident hypertension among PLWH have not been well characterized. In this study, we aimed to determine the time course, sex differences and factors associated with incident hypertension in PLWH initiating ART. Methods and results We conducted a retrospective study in which we used programmatic data from the ART registry to identify sex differences in the determinants of incident hypertension among PLWH initiating the ART regimen from Livingstone University Teaching Hospital in Zambia and followed for 8 years. Males developed hypertension earlier, 2 years after initiating ART, compared to 6 years in females. In multivariable analysis, increasing age, baseline systolic blood pressure and baseline mean arterial pressure (MAP) were associated with increased risk for developing incident hypertension. Also, participants who switched to the integrase strand transfer inhibitor, dolutegravir (DTG) or the protease inhibitor, lopinavir boosted with ritonavir were 2 and 3 times more likely to develop hypertension when compared to those on non-nucleoside reverse transcriptase inhibitors (NNRTIs). However, these relationships were abrogated by sex, as self-reported male sex was the major contributor in predicting incident hypertension. While none of the factors remained significantly associated with incident hypertension upon multivariate analysis among females, body mass index (BMI), and use of protease inhibitors remained strongly associated with hypertension among males. Conclusion Our results indicate that the use of protease inhibitors and BMI are important predictors of incident hypertension among males. Thus, blood pressure and BMI should be closely monitored, particularly in males living with HIV on protease inhibitors. In addition, identifying specific factors that protect females from developing hypertension early is important but remains to be determined.